Visual exploration of fault detection using machine learning and image processing. (2nd December 2022) - Babu, D. Vijendra; Jyothi, K.; Mishra, Divyendu Kumar; Dwivedi, Atul Kumar; Raj, E. Fantin Irudaya; Laddha, Shilpa
The machine learning CNN method defect detection is highly reliant on the training data; thus, post-classification regularisation may significantly improve the output. The suggested fault detection process may perform well on demanding synthetic and actual information by using a practical synthetic fault system depending on the SEAM model. We further propose the visual exploration be made more reliable regarding fault tolerance. The visual exploration model is made up of three-phase namely, visual identification and mapping, dynamic controller, and terminate criterion. The submap-dependent on visual mapping phase ensures higher mapping manageability, semantic classification dependent on active controller ensures continuous driving, and a new completion assessment technique ensures robust re-localisation under the terminate criterion. To preserve mapping and improve visual tracking, all the components are tightly linked. The proposed model machine learning CNN model is examined, and actual tests show fault-tolerance methods are proven to withstand visual monitoring and mapping failure situations.